Modulation index effect on inverter based induction motor drive - Akhilesh Sharma; Anandh N.; Sarsing Gao (Institute of Advanced Engineering and Science, 2020)
Due to a substantial increase in the use of inverter for numerous electrical appliances starting from domestics to industrial drives, an inverter may be directly connected to the power grid system. The dependency on an inverter has been increased over the years. Hence, the proper and efficient design of the inverter will lead to higher efficiency. One of the major challenges is the generation of suitable gate pulses for power switching devices, which in turn depends on the modulation index. The selection of proper modulation index will help in the production of the rated voltage. If the modulation index is less, the duration of on-time pulses will be less and hence, the device's conduction time is also less, thereby the output voltage of the inverter is reduced. A reduced voltage, when applied to an induction motor will have lower speed and even its performance will be sluggish. The speed of the motor improves when it is operated in a closed-loop for the same modulation index. This research paper tries to bring out the effect of modulation index on speed control of an induction motor based on an inverter for both open as well as closed-loop operation. The simulated results indicate that the modulation index in the vicinity to unity will provide rated voltage for the smooth operation of the motor.